Pengaruh Efisiensi Operasional, LDR Terhadap Profitabilitas Memediasi Kecukupan Modal Pada Sektor Perbankan - Aisyah Dwi Nur Rahmah; Syaiful (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2026)
This study examines the effect of Operating Expenses to Operating Income and Loan to Deposit Ratio on Return on Assets, with Capital Adequacy Ratio as a mediating variable in conventional banks listed on the Indonesia Stock Exchange during 2021–2025. The study employed a quantitative approach using secondary data obtained from annual financial reports. The sample consisted of 10 conventional banks selected through purposive sampling, resulting in 50 observations. Data were analyzed using multiple linear regression and Sobel Test. The results indicate that Operating Expenses to Operating Income has no significant effect on Return on Assets, while Loan to Deposit Ratio has a positive and significant effect on Return on Assets. In addition, Capital Adequacy Ratio is unable to mediate the effect of Operating Expenses to Operating Income and Loan to Deposit Ratio on Return on Assets. These findings suggest that bank profitability is more influenced by the effectiveness of credit distribution than by operational efficiency or capital adequacy.